Hidden cues for approach and avoidance motivation: implicit cognitive associations among patients with Nonadherence to HIV treatment. Issue 10 (3rd October 2022) - Houston, Eric; Mindry, Deborah; Alvarado, Eric; Kim, Joshua J.; Evans, Justine; Tarn, Derjung M.
ABSTRACT: Although patient motivation related to HIV treatment is widely acknowledged as a key factor related to consistent adherence and engagement with medical care, research has predominantly focused on explicit rather than implicit cognitive processes that underlie motivation. This study identified and examined implicit cognitive processes that influence approach and avoidance treatment motivation in a sample of 30 HIV patients with suboptimal adherence and poor engagement with medical care. Study participants were predominantly African American (87%) and gay/bisexual (63%). We examined 173 thought statements about treatment collected from patients during two previous studies. Thematic analysis described how implicit cognitive associations influenced patients to approach or avoid treatment and medical care. Findings revealed three major contextual categories of treatment-related thoughts: links with routines and habits, connections to physical changes and reactions, and interpersonal associations. Within each category, implicit cognitive associations about treatment in terms of these daily life events and experiences cued approach and avoidance motivational tendencies without the patient's awareness. Findings from this study support the need for interventions that use implicit, less effortful approaches aimed at promoting adherence and improving the retention of patients with poor engagement.